2020
DOI: 10.31545/intagr/124388
|View full text |Cite
|
Sign up to set email alerts
|

Seed yield and physiological responses to deal with drought stress and late sowing date for promising lines of rapeseed (<i>Brassica napus</i> L.)

Abstract: The introduction of new genotypes of crop plants is among the most strategic research programmes, especially in arid and semi-arid regions. To study the effect of drought stress on seed yield and some physiological traits of promising lines of rapeseed at different sowing dates, an experiment was conducted for two years (2015-2017) in a semi-arid region of Iran. In this research, two conventional sowing dates were set in October 12 and November 1 (late sowing). Irrigation was carried out at two levels: normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, despite the inappropriate distribution of rainfall in the second year of the experiment under late sowing conditions, the ES Hydromel cultivar was able to keep the LRWC at a higher level. The results regarding the late planting date and late-season drought stress showed an increased SR among the studied cultivars under the experimental condition which is in the same direction with the results of other researchers (Shirani Rad et al, 2014b;Moradi Aghdam et al, 2018;Teymoori et al, 2020). In response to drought stress, the plant may have closed the stomata as the most vital strategy to slow down perspiration and prevent the spread of water deficiency in the tissues.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, despite the inappropriate distribution of rainfall in the second year of the experiment under late sowing conditions, the ES Hydromel cultivar was able to keep the LRWC at a higher level. The results regarding the late planting date and late-season drought stress showed an increased SR among the studied cultivars under the experimental condition which is in the same direction with the results of other researchers (Shirani Rad et al, 2014b;Moradi Aghdam et al, 2018;Teymoori et al, 2020). In response to drought stress, the plant may have closed the stomata as the most vital strategy to slow down perspiration and prevent the spread of water deficiency in the tissues.…”
Section: Discussionsupporting
confidence: 87%
“…The GT-biplot analysis also showed that CT was negatively correlated with GMP, STI, MP, HM, WP, Yp, and Ys. Therefore, CT measurement should be introduced as a practical and immediate method to evaluate the drought tolerance of rice genotypes (Yan et al, 2012;Khorsand et al, 2020;Teymoori et al, 2020). Similar to the present study, Sharifi and Ebadi (2018) and Sabouri et al (2022) also used a GT-biplot analysis to identify superior rice genotypes under drought stress conditions.…”
Section: Figmentioning
confidence: 78%
“…Since the CT depends on the transpiration rate, water absorption capacity, and water productivity, a low CT indirectly indicates the high ability of roots to absorb (Yan et al, 2012). Also, since CT is correlated with crop RWC and yield, genotypes with a lower CT show an improved water potential and will have more tolerance to drought stress (Khorsand et al, 2020;Teymoori et al, 2020). 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation